PENDAMPINGAN ORANG TUA TENTANG POLA ASUH POSITIF DI ERA DIGITAL DALAM MENUMBUHKAN KARAKTER ANAK ZAMAN - Indaria Tri H; Indri Dwi I; Mira Pradipta A; Norma Diana F; Sri Nurhidayah; Sulistiyani, Sulistiyani; Noviardani Kartika P; Denok Julianingsih; Soemarmi, Soemarmi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Family is the first place where children can form their character. Technological advances have a significant influence on people's lives, including within the family sphere. Efforts made by parents to form good character in children require positive parenting patterns. This activity aims to provide knowledge regarding positive parenting patterns to shape the character of today's children in Kedungkembar Village, Sidoarjo City, with 30 parents assisting participants who are members of the Parents and Students Association. This research method uses a qualitative descriptive research approach. Service providers provide material related to forming good character for children and how to form good character in children through positive parenting patterns. The results of this research obtained three factors, namely (1) internal factors including: Instinct/instinct, custom/habit, will/desire, inner voice/conscience and heredity), (2) external factors including: (a ) Education, (b) Environment: Family Environment, School Environment, Community Environment, (3) Influence of Technology. The conclusion shows that after mentoring, parents gain new knowledge about character and positive parenting patterns. This activity is beneficial for partners because with this mentoring activity, parents who join the Parents and Students Association gain knowledge about positive parenting styles in forming good character for today's children.